What Every Cardiologist Should Know About Contraception and Reproductive Planning in 2025 - Leslie Cho; Joan E. Briller; Haywood L. Brown; Daniela R. Crousillat; Deirdre J. Mattina; Amy A. Sarma; Nandita S. Scott; Jyoti Sharma; Rachel Sinkey; Stephanie Teal; Kathryn J. Lindley (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Recent studies have shown that maternal mortality continues to increase for all racial and ethnic groups in the United States. The recent changes in reproductive legal policies combined with unacceptably high morbidity and mortality rates have made it crucial for every cardiologist to understand and engage with reproductive planning. The risk of cardiovascular complications during pregnancy is prohibitively high for patients in the modified World Health Organization Risk Class IV with maternal cardiovascular event rates of >40%, and pregnancy is not recommended. It is critical that cardiologists partner with primary care providers, Obstetrics and Gynecology, Complex Family Planning subspecialist, Maternal‐Fetal Medicine specialists, Anesthesia, and Pharmacist and Nursing to implement available contraception strategies and understand termination options that can be offered to these high‐risk patients. The aim of this article is to review risks and advantages of available contraception and pregnancy termination options as it pertains to these high‐risk cardiac patients.